'My aunt was always doing wild things': the long-term impact of Dartington Theatre Training on theatre and community in south-east London 1978–2017. Issue 3 (2nd September 2018) - Slater, David
Abstract : '"My aunt was always doing wild things"' traces the ongoing ripple effect of a question posed by Dartington College in a submission to the Council of Europe in 1983 for a week-long seminar on Theatre and Communities: 'What contribution can theatre practice make to the welfare of the community in which it occurs?' By focusing on one point of radical theatre practice happening within a south London Care Home for older people in 2017 the article seeks to describe ways in which the ecology and pedagogy of Dartington College in the 1970s and 1980s continues to have direct influence on a network of artists and creative producers working in south-east London 40 years later. The paper outlines the innovate practices that underpinned the development of Dartington's four-year Theatre Language course (1978–1985), notably the skills used to negotiate and establish sustained relationships between theatre, people and place. It illustrates how the processes of unlearning and not-knowing supported Theatre Language students to engage openly with the complexity of real contexts.